2004
DOI: 10.1172/jci200419971
|View full text |Cite
|
Sign up to set email alerts
|

Bim regulation may determine hippocampal vulnerability after injurious seizures and in temporal lobe epilepsy

Abstract: Programmed cell death pathways have been implicated in the mechanism by which neurons die following brief and prolonged seizures, but the significance of proapoptotic Bcl-2 family proteins in the process remains poorly defined. Expression of the death agonist Bcl-2-interacting mediator of cell death (Bim) is under the control of the forkhead in rhabdomyosarcoma (FKHR) transcription factors. This prompted us to examine the response of this pathway to experimental seizures and in hippocampi from patients with in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(56 citation statements)
references
References 51 publications
3
52
0
1
Order By: Relevance
“…6A-F). In contrast, and in accordance with our previous data (Araki et al, 2002;Shinoda et al, 2004a;Shinoda et al, 2004b), in sham treated control animals neither the contralateral hippocampus, nor any other brain region, was affected by the KA-induced seizures (Fig. 6A,D).…”
Section: Reduction Of Ka-induced Brain Injury By Adenosine-releasing supporting
confidence: 93%
See 2 more Smart Citations
“…6A-F). In contrast, and in accordance with our previous data (Araki et al, 2002;Shinoda et al, 2004a;Shinoda et al, 2004b), in sham treated control animals neither the contralateral hippocampus, nor any other brain region, was affected by the KA-induced seizures (Fig. 6A,D).…”
Section: Reduction Of Ka-induced Brain Injury By Adenosine-releasing supporting
confidence: 93%
“…One week after cell transplantation, animals received unilateral stereotaxic microinjection of kainic acid (KA) into the basolateral amygdala nucleus based on stereotactic coordinates relative to bregma: AP = -0.94 mm, L = -2.85 mm, V = -3.75 mm (Franklin and Paxinos, 1997) as described (Araki et al, 2002;Shinoda et al, 2004b).…”
Section: Seizure Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Most importantly, spontaneous seizures in Adk-tg mice appear to be non-injurious, indicating that the increased susceptibility to neuronal cell death (Fig. 4) is related to the spread of injurious KA-induced acute type IV seizures (Shinoda et al, 2004;Henshall and Simon, 2005). Our findings further imply that tight regulation of adenosine levels by ADK is a necessity and that moderate overexpression of ADK in the absence of astrogliosis or epileptogenesis is sufficient to induce spontaneous seizures (i.e.…”
Section: Spontaneous Seizures In Adk-tg Micementioning
confidence: 53%
“…The upregulation of Bim is JNK dependent in mice since it is blocked by SP600125 (Murphy et al, 2010), although FoxO1 or 3a may also be important (Murphy et al, 2010;Shinoda et al, 2004). Bim is also upregulated after pilocarpine-induced seizures (Yang et al, 2007), but Bim levels were reported to decline after seizures caused by intraventricular KA (Korhonen et al, 2003).…”
Section: Bim Activation and Knockout Phenotype In Status Epilepticusmentioning
confidence: 99%